Meningkatkan Hasil Belajar IPA Peserta Didik Kelas V Pada Materi Tumbuhan Hijau dengan Menggunakan Metode Inquiri Sekolah Dasar Negeri Wasian Kecamatan Dimembe Kabupaten Minahasa Utara - Anneke Pontoh (Jurnal Ilmiah Wahana Pendidikan, 2022)
This classroom action research is motivated by the not yet optimal science learning process where learning only runs in one direction and is not in accordance with the learning implementation plan, the learning process is more dominated by the teacher, and the teacher has not used methods and media that are in accordance with the material. The purpose of this classroom action research is to describe the improvement of students' science learning outcomes on Green Plants material using the Inquiry method in class V SD Negeri Wasian, Dimembe District, North Minahasa Regency. This classroom action research procedure is guided by Suharsimi's theory with 4 steps, namely: planning, implementing, observing and reflecting. The subjects in this classroom action research were 20 graders of the Wasian State Elementary School, Dimembe District, North Minahasa Regency. The data collected and analyzed are quantitative data derived from student learning outcomes and qualitative data derived from student observations during the learning process. The research instrument includes a test result sheet, observation sheet and documentation. This research was carried out in two cycles, each cycle consisting of 2 meetings. In the first cycle the value of student learning outcomes who completed totaled 12 people with classical completeness 52.38%, with the low learning outcomes, the researchers continued research in cycle II. Meanwhile, in the second cycle, 15 students completed the classical completeness with 76.20% who had achieved the indicator of success, namely 75%. Based on the results of the study, it can be concluded that the Inquiry method can improve students' science learning outcomes on Green Plants material in class V of Wasian State Elementary School, Dimembe District, North Minahasa Regency